Epidemiology and pathology of Trichomonas gallinae in the common pigeon (Columba livia) (Journal of the Bangladesh Agricultural University, 2010)
Pigeons (n=300) were examined during July 2007 to June 2008 in different areas of Mymensingh district. Of the pigeons examined, 202 (67.3%) were infected by Trichomonas gallinae (Rivolta, 1878). Prevalence of Trichomonas gallinae was higher in female pigeon (70.9%) than male pigeon (63.8%). Adult pigeons aged >3 months were comparatively more affected (75%) than the squab aged